ANALYSIS OF LEARNING MOTIVATION BETWEEN MALE AND FEMALE STUDENTS OF ELEMENTARY SCHOOL X DURING ONLINE LEARNING DURING THE COVID-19 PANDEMIC - Jonherz Stenlly Patalatu; Alpres Tjuana; Sri Astri Boteme (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses whether there is a difference between male and female students learning motivation during online learning amidst the COVID-19 pandemic or not. The research is quantitative research, which has 30 high-grade students at elementary school “X” in Tobelo. as the sample “X” in Tobelo. The results indicate that there are no significant differences between male and female students learning motivation in which the mean score for male students' learning motivation was 46.13 and the mean score of female students’ learning motivation was 45.27 with a significance value of p > 0.05 (0.342 > 0.05). It implies that although the learning was conducted online during the COVID-19 pandemic, male and female students had similar learning motivations.